Usability and Workflow Evaluation of “RhEumAtic Disease activitY” (READY) - Yen, Po-Yin; Lara, Barbara; Lopetegui, Marcelo; Bharat, Aseem; Ardoin, Stacy; Johnson, Bernadette; Mathur, Puneet; Embi, Peter J.; Curtis, Jeffrey R. (Applied Clinical Informatics, 2016)
Background RhEumAtic Disease activitY (READY) is a mobile health (mHealth) application that aims to create a shared platform integrating data from both patients and physicians, with a particular emphasis on arthritis disease activity.Methods We made READY available on an iPad and pilot implemented it at a rheumatology outpatient clinic. We conducted 1) a usability evaluation study to explore patients’ and physicians’ interactions with READY, and 2) a time motion study (TMS) to observe the clinical workflow before and after the implementation.Results A total of 33 patients and 15 physicians participated in the usability evaluation. We found usability problems in navigation, data entry, pain assessment, documentation, and instructions along with error messages. Despite these issues, 25 (75,76%) patients reported they liked READY. Physicians provided mixed feedback because they were concerned about the impact of READY on clinical workflow. Six physicians participated in the TMS. We observed 47 patient visits (44.72 hours) in the pre-implementation phase, and 42 patient visits (37.82 hours) in the post-implementation phase. We found that patients spent more time on READY than paper (4.39mins vs. 2.26mins), but overall, READY did not delay the workflow (pre = 52.08 mins vs. post = 45.46 mins). This time difference may be compensated with READY eliminating a workflow step for the staff.Conclusion Patients preferred READY to paper documents. Many found it easier to input information because of the larger font size and the ease of ‘tapping’ rather than writing-out or circling answers. Even though patients spent more time on READY than using paper documents, the longer usage of READY was mainly due to when troubleshooting was needed. Most patients did not have problems after receiving initial support from the staff. This study not only enabled improvements to the software but also serves as good reference for other researchers or institutional decision makers who are interested in implementing such a technology.Citation: Yen P, Lara B, Lopetegui M, Bharat A, Ardoin S, Johnson B, Mathur P, Embi P, Curtis J. Usability and workflow evaluation of “RhEumAtic Disease activitY” (READY).
Keywords: Rheumatoid arthritis; mobile health; disease activity; time motion study; mobile application; mHealth; workflows and human interactions; mobile computing and communication; usability